Crystal-liquid Fugacity Ratio as a Surrogate Parameter for Intestinal Permeability - Parvin Zakeri-Milani; Zohreh Fasihi; Jafar Akbari; Ensieh Jannatabadi; Mohammad Barzegar-Jalali; Raimar Loebenberg; Hadi Valizadeh (Frontiers Media S.A., 2016)
Background: We assessed the feasibility of using crystal-liquid fugacity ratio (CLFR) as an alternative parameter for intestinal permeability in the biopharmaceutical classification (BCS) of passively absorbed drugs. Methods: Dose number, fraction of dose absorbed, intestinal permeability, and intrinsic dissolution rate were used as the input parameters. CLFR was determined using thermodynamic parameters i.e., melting point, molar fusion enthalpy, and entropy of drug molecules obtained using differential scanning calorimetry. Results: The CLFR values were in the range of 0.06-41.76 mole percent. There was a close relationship between CLFR and in vivo intestinal permeability (r > 0.8). CLFR values of greater than 2 mole percent corresponded to complete intestinal absorption. Applying CLFR versus dose number or intrinsic dissolution rate, more than 92% of tested drugs were correctly classified with respect to the reported classification system on the basis of human intestinal permeability and solubility. Conclusion: This investigation revealed that the CLFR might be an appropriate parameter for quantitative biopharmaceutical classification. This could be attributed to the fact that CLFR could be a measure of solubility of compounds in lipid bilayer which was found in this study to be directly proportional to the intestinal permeability of compounds. This classification enables researchers to define characteristics for intestinal absorption of all four BCS drug classes using suitable cutoff points for both intrinsic dissolution rate and crystal-liquid fugacity ratio. Therefore, it may be used as a surrogate for permeability studies.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.